Occupational neurology - Lotti, Marcello; Bleecker, Margit L.; ScienceDirect eBooks (Amsterdam, Netherlands : Elsevier, 2015)
Occupational Neurology a volume in the Handbook of Clinical Neurology Series, provides a comprehensive overview of the science, clinical diagnosis, and treatment for neurotoxin related neurological and psychiatric disorders. This timely collection provides not only a complete scientific reference on the chemical origin of this class of neurological and psychiatric disorders, but also a practical guide to diagnosis and treatment challenges and best practices. Handbook of Clinical Neurology Series The first volume of the Handbook of Clinical Neurology under the editorship of George Bruyn and Pierre Vinken was published in 1968. In 1982, the series was brought to an interim conclusion with the publication of the cumulative index volume (Volume 44). By that stage, the Handbook had come to represent one of the largest scientific works ever published. It enjoys a high reputation in specialist media circles throughout the world. After the series was concluded in 1982, it was realized that an update of the material was imperative. Accordingly, a revised series was planned and published over the following years, concluding with the publication of another cumulative index to both series (Volume 76-78) in 2002. Since then, George Bruyn has passed away and Pierre Vinken has retired, but the need for a further new series, incorporating advances in the field, again become necessary. Professors Michael J. Aminoff, François Boller and Dick F. Swaab have with enthusiasm taken on the responsibility of supervising the preparation of a third series, the first volumes of which were published in 2003. Now, more than 130 volumes after the first published, the Handbook of Clinical Neurology series continues to have an unparalleled reputation for providing the latest foundational research, diagnosis, and treatment protocols essential for both basic neuroscience research and clinical neurology. Provides comprehensive coverage of neurotoxins, especially in the workplace Details the latest science as the foundation for neurotoxicity diagnosis and treatment Presents coverage of the diagnosis and treatment essential for clinical neurologists and occupational medicine specialists.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed November 18, 2015).
Elsevier
Keywords: Neurology; Nervous system -- Diseases -- Treatment; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Nervous system -- Diseases -- Treatment; Neurology; Nervous System Diseases -- therapy; Occupational Diseases; Electronic books